Satellite based long-term evaluation of bush encroachment on sourish-mixed veld at the Towoomba Reseach Station in Bela Bela, Limpopo Province - Mpati, Thabo Michael (My University, 2015)
Savannas are the most important ecosystems for raising livestock in Africa. In the past 50 years, evidence has shown that savannas throughout the world are being altered by bush encroachment. This is an ecological succession process where perennial plants such as shrubs and trees replace annual vegetation. This reduces the amount of palatable fodder and directly threatens livestock productivity in many localities. This study evaluated long-term bush encroachment using multi-date Landsat Thematic Mapper (TM) images 1989, 1990, 1993, 1995, 1999, 2004 and 2008 to reconstruct changes in spatial distribution of trees and shrubs at the Towoomba Reseach Station over a period of 19 years, from 1989 to 2008. Grasses and woody species were classified using unsupervised classification and Normalised Difference Vegetation Index was used to assess forage productivity and change in vegetation with years. The study was carried out at Towoomba Research Station in Bela Bela, Limpopo Province, South Africa. The study revealed that bush encroachment is a natural process and is independent of the grazing patterns. The results show that if not monitored encroaching species will make it difficult for grazers to get underneath the trees and also disturb the photosynthetic process of grass thereby replacing the grass. The study further showed that satellite remote sensing has the potential for monitoring rangeland quality. Keywords: Bush encroachment, remote sensing, classification and Normalised Difference Vegetation Index
Thesis (MSc. Agriculture (Remote Sensing)) -- University of Limpopo, 2015
Keywords: Remote sensing; Bush encroachment; Rangelands -- Monitoring.; Veld grass -- South Africa -- Limpopo.; Veld -- Management.